Aesthetics of Forgiveness: Representing Forgiveness Artistically - Brown, Frank (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
Although one major form of theological aesthetics today is aesthetics of divine revelation, there is an important role for a theological aesthetics focused more on art and culture, with attention to ethics as well. This paper explores the potentially transformative power of the art of fiction, in its ethical and theological dimension, partly through an analysis of the novel Gilead by Marilynne Robinson. The discussion attends to the novel’s ways of showing the limitations of human judgment, the difficulty of forgiveness, and yet the way in which even imperfect forms of forgiveness can be graced, becoming a blessing.